ANALYSIS OF LAND OWNERSHIP DISPUTES IN THE KANJENGAN SHOPPING COMPLEX, SEMARANG CITY - Suroto Suroto (Universitas 17 Agustus 1945 Semarang, 2023)
The study aimed to determine and analyze the legal considerations of judges regarding the ownership of disputed land rights in the Kanjengan Shopping Complex and the legal status of disputed ownership of land rights in the Kanjengan Shopping Complex. The approach method used in this study is a normative juridical approach with a case approach. This research is a descriptive analysis. The data analysis method used in this study is a qualitative descriptive data analysis method. The results of the study stated that the judge’s legal considerations regarding land ownership disputes in the Kanjengan shopping complex included the Building Use Rights certificate owned by the Plaintiff, which had been issued by the National Land Agency following the applicable procedures and had complied with statutory provisions, namely Article 19 paragraph (2) of the Law No. 65 of 1960 concerning the Basic Agrarian Law juncto Article 32 paragraph (1) Government regulations (PP) No. 24 of 1997 concerning Land Registration juncto Article 1870 of the Civil Code in conjunction with Article 165 HIR where the HGB certificate is. The legal status of the ownership of land rights in dispute in the Kanjengan shopping complex is the legal owner/holder of land and building rights located in the Kanjengan Complex, Semarang, based on a Certificate of Building Use Rights and a Building Permit issued by the competent authority (Semarang City National Land Agency).